1985
DOI: 10.1021/np50040a015
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids of Tunicates, III. The Structural Elucidation of Two New Marine Carotenoids, Amarouciaxanthin A and B

Abstract: The structure of two new marine carotenoids, isolated from the tunicate, Amaroucium pliciferum, and designated as amarouciaxanthin A and B, were determined on the basis of chemical and spectral data. Amarouciaxanthin A was determined as (6S, 3'S, 5'R,6'R)- 6,3',5'-trihydroxy-4,5,6',7'-tetradehydro-7,8,5',6'-tetrahydro-beta, beta-carotene-3,8-dione, and Amarouciaxanthin B was determined as (6S,3'R)-6,3'-dihydroxy-4,5,7',8'-tetradehydro-7,8-dihydro-beta,beta- carotene-3,8-dione. These two compounds are also pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 12 publications
3
34
0
Order By: Relevance
“…Until now, amarouciaxanthin A has been found only in two marine invertebrates, a tunicate (A. pliciferum) (Matsuno et al, 1985a) and a bivalve (P. euglypta) (Matsuno et al, 1985b). From the structural similarity, Matsuno et al (1985a) hypothesized that amarouciaxanthin A would be one of the metabolites of fucoxanthin in A. pliciferum. However, there has been no experimental evidence for the conversion of fucoxanthin into amarouciaxanthin A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, amarouciaxanthin A has been found only in two marine invertebrates, a tunicate (A. pliciferum) (Matsuno et al, 1985a) and a bivalve (P. euglypta) (Matsuno et al, 1985b). From the structural similarity, Matsuno et al (1985a) hypothesized that amarouciaxanthin A would be one of the metabolites of fucoxanthin in A. pliciferum. However, there has been no experimental evidence for the conversion of fucoxanthin into amarouciaxanthin A.…”
Section: Discussionmentioning
confidence: 99%
“…at ASPET Journals on May 12, 2018 dmd.aspetjournals.org ciaxanthin A, which has been isolated from marine animals, a tunicate (Amaroucium pliciferum) (Matsuno et al, 1985a), and a bivalve (Paphia euglypta) (Matsuno et al, 1985b).…”
Section: Hepatic Conversion Of Fucoxanthinol Into Amarouciaxanthin Amentioning
confidence: 99%
“…They are widely distributed in various tunicates. Amarouciaxanthin A ( 34 ) and amarouciaxanthin B ( 69 ), having a unique 3-oxo-6-hydroxy-ε-end group, were first isolated from the tunicate Amaroucium pliciferum [35] (Figure 12). Peridinin and its metabolites are also found in tunicates.…”
Section: Protochordata (Tunicates)mentioning
confidence: 99%
“…In addition to rodents, it has been reported that fucoxanthin is absorbed in other animals such as tunicates [37,38], chicken [39], and aquatic insects [40]. However, fucoxanthin was not absorbed in freshwater fish [40].…”
Section: Intestinal Absorption Of Xanthophyllsmentioning
confidence: 99%